2015
DOI: 10.1002/chem.201405724
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical CaCO3 Chromatography: A Stationary Phase Based on Biominerals

Abstract: In biomineralization, acidic macromolecules play important roles for the growth control of crystals through a specific interaction. Inspired by this interaction, we report on an application of the hierarchical structures in CaCO3 biominerals to a stationary phase of chromatography. The separation and purification of acidic small organic molecules are achieved by thin-layer chromatography and flash chromatography using the powder of biominerals as the stationary phase. The unit nanocrystals and their oriented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…The peculiar performance of biominerals originates from their hierarchical architectures that are comprised of nanograins aligned in specic directions. 9,[38][39][40][41][42][43] Mesocrystals are basically thought to be formed through particle-mediated self-assembly as a nonclassical crystallization process. 33,34 Rectangular nanoblocks, such as nanocubes and nanocuboids, are accumulated on a substrate by a lateral capillary force [44][45][46][47][48] at the vapor-liquid-solid interface and a depletion force between neighboring particles by the evaporation of a liquid medium.…”
Section: Introductionmentioning
confidence: 99%
“…The peculiar performance of biominerals originates from their hierarchical architectures that are comprised of nanograins aligned in specic directions. 9,[38][39][40][41][42][43] Mesocrystals are basically thought to be formed through particle-mediated self-assembly as a nonclassical crystallization process. 33,34 Rectangular nanoblocks, such as nanocubes and nanocuboids, are accumulated on a substrate by a lateral capillary force [44][45][46][47][48] at the vapor-liquid-solid interface and a depletion force between neighboring particles by the evaporation of a liquid medium.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that CaCO 3 -PMAcO behaved as a reversed-phase mode stationary phase for the separation of naphthalene and alkylbenzenes, while pure CaCO 3 generally works as normal-phase mode stationary phase. 7 The octadecene groups of the CaCO 3 -PMAcO microspheres at the stationary phase to mobile phase interface performed a role identical to the octadecyl groups of ODS, resulting in reversedphase characteristics. During the separation of a mixture of 11 alkylbenzenes, all peaks could be clearly observed with a baseline resolution (peak resolution R s = 1.8-4.2 4 1.5) in the chromatogram (Fig.…”
Section: Evaluation Of Caco 3 -Pmaco Microspheres As a Column Packingmentioning
confidence: 99%
“…5,6 Paying attention to the hierarchical structure of biominerals to control the distribution of substances, a normal phase chromatography stationary phase based on biopolymer-removed crushed seashells has been developed. 7 Although it was shown that the hierarchical structure of biominerals can be applied to a chromatographic separation material, the functionality of the biopolymer of biominerals like egg shells in terms of controlling substance distribution was not fully used for separation purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The hierarchical structures of biominerals were used as the functional materials themselves, self-templates, and templates in previous studies. [6][7][8][9] For example, CaCO 3 biominerals themselves were applied to an adsorbent of gases and heavy metal ions and a stationary phase of chromatography. 6,7 The silica skeleton of a diatom served as the self-template for the preparation of a silicon hierarchical structure with enhanced electrochemical properties.…”
mentioning
confidence: 99%
“…[6][7][8][9] For example, CaCO 3 biominerals themselves were applied to an adsorbent of gases and heavy metal ions and a stationary phase of chromatography. 6,7 The silica skeleton of a diatom served as the self-template for the preparation of a silicon hierarchical structure with enhanced electrochemical properties. 8 While biological resources were used as templates for synthesis and morphology control of inorganic materials, 9,10 the approaches were not fully applied to those of organic materials.…”
mentioning
confidence: 99%